Grascophobia Among Student of University of Social Welfare and Rehabilitation Science - Soheila Ebrahimi; Reza Laripour; Hamed Ghyasi; Maryam Ramshini; Ahmad Delbari (Sālmand, 2020)
Objectives: This study considering grascophobia and its related factors in University of Social Welfare and Rehabilitation Science. Methods & Materials: This study is cross-sectional and we used available sampling. A Persian translation of Ageing Anxiety Scale (AAS) was administered to the university students. Results: The total Mean±SD is 70.08±9.69. The scale has 4 subscale and higher level is fear of lost: mean is 20.14; also between 17 factors 3 factors has statistical significance. Different academic year (F=2.21; Sig.=0.05), satisfying of major (F=2.34; Sig.=0.44) if their fathers age was 60 and more (T=2.18; Sig.=0.031). SD is 4.84 and lower level is fear of older people: Mean±SD is 14.19±5.08. Conclusion: According to the results we suggest to reduce grascophobia by educate students about aging.